Calvin's Anthropological View and the Development of the Third Word Theology of Mission with Special Refeence to Kosuke Koyama's Doctrine f Human Beings - Robbyanto Notomiharjo (STT Amanat Agung, 2007)
Calvin's Anthropological View and the Development of the Third Word Theology of Mission with Special Refeence to Kosuke Koyama's Doctrine f Human Beings